Research on Influence of TiSi(N) Reflective Coating Thermal Resistance on Energy Absorption of Fireproof Textile Coupled with Auxetic Fabric - MIEDZIŃSKA, Danuta; STANKIEWICZ, Michał; GIELETA, Roman; MARSZAŁEK, Konstanty (Engineering Transactions, 2019)
The research presented in the paper deals with the improvement of firemen protective clothing. The proposed modification of the special textile PROTON is based on the application of TiSi(N) nanocomposite reflective layer, which improves the thermal resistance of the coated material. The second improvement deals with the implementation of auxetic textile into the protective clothing structure. Such material is characterized with the very good blast wave resistance. In the paper both phenomena were studied. The results of thermal resistance of coated and not coated PROTON shown that the application of such structure decreased the temperature acting behind the textile and the application of the auxetic textile significantly increased the PROTON resistance to gas impact. Also the advantages of coupling both improvement methods were discussed, because of the negative influence of high temperature on auxetic behaviour.